A sodium ion battery negative electrode slurry and a method for preparing a negative electrode slurry thereof

By adding porous medium and highly substituted hydroxypropyl cellulose to the hard carbon anode of sodium ion batteries, a porous coating structure is formed, which solves the problem of poor rate performance of hard carbon anode during high-rate charging and discharging, and significantly improves the rate performance and cycle stability of the battery.

CN115188965BActive Publication Date: 2025-03-25JIANGSU ZOOLNASM ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210849289.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-03-25
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

The hard carbon negative electrode material in sodium ion batteries has poor rate performance during high-rate charging and discharging, resulting in insufficient channels for sodium ions to be embedded and disengaged.

Method used

By adding porous media, such as porous anatase titanium dioxide or porous alumina to the hard carbon negative electrode system, the channel for embedding and disengagement of sodium ions is increased, and the use of porous coated structure and the use of highly substituted hydroxypropyl cellulose is formed to improve the rate performance of the negative electrode.

Benefits of technology

It significantly improves the rate performance of hard carbon anode in sodium ion batteries, increases the channel for the embedding and disengagement of sodium ions, and improves the cycle stability and high-rate charging and discharging capabilities of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115188965B_ABST
    Figure CN115188965B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of sodium ion batteries, and specifically relates to a sodium ion battery negative electrode slurry and a method for preparing a pole piece thereof, wherein the slurry comprises a negative electrode active material, a porous medium, a conductive agent, a binder, a thickener and a solvent, and the mass ratio of the slurry comprises: 80-99.9 parts of negative electrode active material, 0.1-5 parts of porous medium, 0.1-10 parts of conductive agent, 0.1-10 parts of binder, 0.1-5 parts of thickener, 70-300 parts of solvent, and provides a method for preparing the slurry and a method for preparing a pole piece. The present invention improves the negative electrode rate performance of the sodium ion battery by adding a small amount of porous medium to the negative electrode slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode slurry and a method for preparing a pole piece thereof. Background Art

[0002] Sodium-ion batteries have a very similar working principle to lithium-ion batteries. Sodium resources are extremely abundant and the production cost of sodium-ion batteries is low. Therefore, sodium-ion batteries are considered to be ideal energy storage devices for the development of future new energy fields.

[0003] The negative electrode material used in traditional lithium-ion batteries is graphite. However, since sodium cannot form a stable binary compound Na-C with graphite, the capacity of graphite to embed sodium is actually very low and cannot be directly used as a negative electrode material for sodium-ion batteries. At present, sodium-ion batteries mainly use hard carbon or soft carbon as negative electrode materials. This is because hard carbon or soft carbon has a long-range disordered and short-range ordered structure, and the interlayer spacing is large, which can meet the embedding and extraction of sodium ions and has good cycle performance. However, due to the large radius of sodium ions, sodium ions cannot be embedded in and extracted from hard carbon in time during high-rate charge and discharge, resulting in poor rate performance of hard carbon in sodium-ion batteries. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a solution to the problem of poor negative electrode rate in sodium ion batteries, using the porous structure of the porous medium to increase the adsorption area, combining the chemical activity of the material itself to form sodium ion adsorption, and increasing the channels for the insertion and extraction of sodium ions.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A sodium ion battery negative electrode slurry comprises a negative electrode active material, a porous medium, a conductive agent, a binder, a thickener and a solvent, and the mass ratio of the slurry comprises: 80-99.9 parts of the negative electrode active material, 0.1-5 parts of the porous medium, 0.1-10 parts of the conductive agent, 0.1-10 parts of the binder, 0.1-5 parts of the thickener and 70-300 parts of the solvent.

[0007] The negative electrode active material is hard carbon or soft carbon.

[0008] The porous medium adopts porous anatase titanium dioxide or porous alumina, and the particle size distribution D10 is 1μm, D50 is 5μm, D90 is 10μm, and Dmax is 12μm. When the porous medium adopts porous anatase titanium dioxide and porous alumina, the porous structure of the medium itself forms a stable large surface, and the surface activity of anatase titanium dioxide and activated alumina can form a stable adsorption of sodium ions, thereby achieving excellent results. Preferably, the porous medium adopts a porous core-shell composite material, and anatase titanium dioxide is used as the surface layer, and porous alumina is wrapped to form a porous coating structure. On this structure, the surface hydroxyl activity of activated alumina can form a stable connection with the surface hydroxyl of anatase titanium dioxide, that is, activated alumina acts as an internal active site to promote the activity of titanium dioxide on the surface, thereby increasing the sodium ion adsorption capacity of the porous medium.The preparation method of the porous coating structure comprises the following steps: placing aluminum hydroxide fine powder in an ethanol-ether solution for microwave cleaning, taking it out and drying it to obtain clean aluminum hydroxide fine powder, wherein the volume ratio of ethanol to ether in the ethanol-ether solution is 3:4, the concentration of the aluminum hydroxide fine powder in the ethanol-ether solution is 400 g / L, the microwave cleaning temperature is 15° C., the power is 400 W, and the drying temperature is 85° C.; the aluminum hydroxide fine powder is a porous structure, and this step utilizes the oscillation of microwave cleaning and the solubility of the ethanol-ether solution to Impurities on the surface of aluminum fine powder; a2, dissolving n-butyl titanate in ether and stirring evenly to form titanium ether liquid, then immersing aluminum hydroxide fine powder in the titanium ether liquid for 15 minutes, filtering and drying to obtain coated aluminum hydroxide fine powder, the concentration of n-butyl titanate in the titanium ether liquid is 150g / L, the stirring speed is 150r / min, the concentration of the aluminum hydroxide fine powder in the titanium ether liquid is 30g / L, the drying temperature is 45°C, and this step forms n-butyl titanate on the surface of aluminum hydroxide fine powder by combining liquid film adsorption and evaporation. a3, placing the coated aluminum hydroxide fine powder in a reactor and allowing it to react at a constant temperature for 2 hours, then introducing nitrogen containing water vapor for 8 minutes, and allowing it to stand for 25 minutes to obtain titanium oxide-coated aluminum oxide; the temperature of the constant temperature reaction is 190°C, the volume proportion of water vapor in the nitrogen is 8%, and the introduction rate is 40mL / min, and the standing temperature is 120°C; this step utilizes aluminum hydroxide to be heated to convert it into activated alumina and release water molecules, and the water molecules directly hydrolyze with n-butyl titanate to form titanic acid and n-butyl titanate at the connection. The active alumina is connected by reaction, and is completely hydrolyzed by secondary infiltration of water vapor to achieve the stable formation of anatase titanium dioxide; a4, the titanium oxide is wrapped by alumina and sintered for 2 hours to obtain a porous coating structure, and the sintering temperature is 190°C; this step utilizes the porous structure of aluminum hydroxide fine powder to form secondary pores during sintering to achieve the purpose of improving the porous performance, and at the same time cooperates with the liquid film coverage of n-butyl titanate to form a surface coating structure, and alumina and titanium dioxide form a stable connection system at the interface based on the surface active groups.

[0009] The conductive agent is one or more materials selected from the group consisting of conductive carbon black, acetylene black, conductive graphite, single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0010] The binder is made of one or more materials selected from styrene-butadiene rubber, polyacrylic acid and polyacrylonitrile.

[0011] The thickener is sodium carboxymethyl cellulose.

[0012] The solvent used was deionized water.

[0013] The method for preparing the negative electrode slurry of a sodium ion battery comprises:

[0014] S1, material preparation: weigh the required slurry raw materials according to the required ratio and dry them in a protective atmosphere;

[0015] S2, glue preparation: placing the thickener and the solvent in a planetary agitator, stirring them in a vacuum at a revolution of 10-100 rpm and a rotation of 500-7000 rpm for 0.5-12 hours to obtain a glue solution, passing cooling water during the stirring process to prevent the glue solution from being too hot; the obtained glue solution needs to be left to stand for 12-24 hours;

[0016] S3, dispersion: add the conductive agent to the glue solution, and stir it in a vacuum at 10-100 rpm and 500-5000 rpm for 0.5-6 hours; then add the negative electrode active material, and stir it in a vacuum at 10-100 rpm and 500-5000 rpm for 0.25-3 hours; then add the porous medium, and stir it in a vacuum at 10-100 rpm and 500-5000 rpm for 0.5-3 hours; finally add the binder, and stir it in a vacuum at 10-100 rpm and 200-1000 rpm for 0.25-2 hours;

[0017] S4, degassing: placing the slurry in a vacuum environment of -0.1 MPa for 20 minutes to 3 hours;

[0018] S5, sieving: the slurry is passed through a 100-300 mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

[0019] The method for preparing a sodium ion electrode negative electrode sheet using the slurry comprises the following steps:

[0020] Step 1, adding highly substituted hydroxypropyl cellulose to the slurry and stirring evenly to obtain a dispersed slurry, wherein the concentration of the highly substituted hydroxypropyl cellulose in the slurry is 2-3%;

[0021] Step 2, coating the dispersed slurry on the current collector, and then rolling at a constant temperature to obtain a prefabricated negative electrode sheet, wherein the current collector is an aluminum foil, and the thickness of the aluminum foil is 8-20 μm; the temperature of the constant temperature rolling is 80-90° C., and the pressure is 0.2-0.5 MPa;

[0022] Step 3, soaking and dissolving the prefabricated negative electrode sheet in methanol, taking it out and drying it to obtain a porous electrode sheet, wherein the mass ratio of the prefabricated negative electrode sheet to methanol is 1:20-30, and the drying temperature is 60-70°C. The dissolved solution is evaporated to recover the highly substituted hydroxypropyl cellulose.

[0023] The present invention adds a porous medium to the traditional hard carbon negative electrode system, disperses the hard carbon around the porous medium, increases the channels for the hard carbon to contact the sodium ions, provides more channels for the embedding and extraction of sodium ions during high-rate charge and discharge, and improves the rate performance of the hard carbon negative electrode in the sodium ion battery. At the same time, the present invention uses the pseudoplasticity and water retention of highly substituted hydroxypropyl cellulose to ensure that the pole piece itself forms a uniform porous structure from top to bottom, and the porous structure brought by the matching material forms a porous system of uneven size. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] FIG. 1 is a comparison diagram of the rate performance of Example 1 and Example 2 of the present invention DETAILED DESCRIPTION

[0025] 1 , a specific embodiment of the present invention is described in detail, but no limitation is imposed on the claims of the present invention.

[0026] Example 1

[0027] A method for preparing a negative electrode slurry for a sodium ion battery comprises:

[0028] S1, add 800g of deionized water and 8g of thickener sodium carboxymethyl cellulose (CMC) powder into a 5L planetary stirring device stirrer, stir for 15 minutes at a revolution of 30 rpm and a rotation of 1000 rpm; open the stirring container, scrape the undissolved powder on the stirring and dispersing disk and the wall of the stirrer into the solution, and stir in a vacuum at a revolution of 30 rpm and a rotation of 2000 rpm for 2 hours and 30 minutes; during the period, cool water is passed to prevent the glue solution from overheating; the stirred glue solution is allowed to stand in a vacuum state for 24 hours;

[0029] S2, add 25g of conductive carbon black into the glue solution, and stir it in vacuum at 30 revolutions / min and 2000 rotations / min for 1 hour;

[0030] S3, adding 1200g of hard carbon, a negative electrode active material of a sodium ion battery, into the above-mentioned mixed glue solution, wherein the specific surface area of ​​the hard carbon is 6m 2 / g, D50 is 5 microns; the mixture is stirred in vacuum at 30 revolutions per minute and 2500 revolutions per minute for 2 hours;

[0031] S4, (4) adding 30 g of anatase titanium dioxide to the above mixed solution, wherein the particle size distribution of the titanium dioxide is D10 of 1 μm, D50 of 5 μm, D90 of 10 μm, and Dmax of 12 μm; and stirring the mixture in a vacuum at a revolution of 30 rpm and a rotation of 2500 rpm for 2 hours;

[0032] S5, adding 40 g of styrene-butadiene rubber latex having a solid content of 40% to the above-mentioned mixed solution, and stirring the mixture in a vacuum at a revolution of 30 rpm and a rotation of 500 rpm for 30 minutes;

[0033] S6, passing the deaerated slurry through a 150-mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

[0034] Preparation of the pole piece: The sieved slurry is evenly coated on a 15 μm thick aluminum foil by slurry drawing, dried in a vacuum oven at 120°C for 12 hours, and the obtained pole piece is rolled to a compaction density of 1.1 g / cm 3 The surface density of the obtained electrode is 4.5 mg / cm 2 .

[0035] Example 2

[0036] This embodiment is a comparative embodiment, and the specific process is as follows:

[0037] The first three steps are consistent with Example 1, except that in step (3), the stirring time is increased to 4 hours, and step (4) is cancelled; the subsequent slurry preparation process and electrode preparation process are consistent with Example 1.

[0038] The pole pieces of the above embodiment were used to prepare button batteries. The specific preparation method was as follows: a metal sodium sheet, a 20-micron-thick polyacrylic acid, and a negative pole piece were stacked in sequence to form an electrode group, which was loaded into a button battery shell, and an electrolyte with sodium hexafluorophosphate as a solute, ethylene carbonate and propylene carbonate in a volume ratio of 1:1 as a solvent, and a solute concentration of 1 mol / L was added. The added volume was 200 μL, and the button battery was assembled; the assembled battery was discharged at a constant current of 0.1C to 0V at a current density of 1C=120mA / g at 25°C, allowed to stand for 5 minutes, and charged at a constant current of 0.1C to 2V, and this process was repeated 3 times; and constant current charging and discharging were performed 3 times at different rates (0.2C, 0.5C, 1C, 2C), and the cut-off voltage was consistent with 0.1C.

[0039] It can be seen from Figure 1 that after adding anatase titanium dioxide, the discharge capacity of the hard carbon negative electrode at 2C rate is increased by 13.7% compared with the negative electrode without adding titanium dioxide. The other rate improvement ratios are shown in the table:

[0040]

[0041] The data in the above table show that adding anatase titanium dioxide can significantly improve the rate performance of hard carbon in sodium ion batteries.

[0042] Example 3

[0043] A method for preparing a negative electrode slurry for a sodium ion battery comprises:

[0044] S1, add 800g of deionized water and 8g of thickener sodium carboxymethyl cellulose (CMC) powder into a 5L planetary stirring device stirrer, stir for 15 minutes at a revolution of 30 rpm and a rotation of 1000 rpm; open the stirring container, scrape the undissolved powder on the stirring and dispersing disk and the wall of the stirrer into the solution, and stir in a vacuum at a revolution of 30 rpm and a rotation of 2000 rpm for 2 hours and 30 minutes; during the period, cool water is passed to prevent the glue solution from overheating; the stirred glue solution is allowed to stand in a vacuum state for 24 hours;

[0045] S2, add 25g of conductive graphite into the glue solution, and stir it in vacuum at 30 revolutions / min and 2000 rotations / min for 1 hour;

[0046] S3, adding 1200g of hard carbon, a negative electrode active material of a sodium ion battery, into the above-mentioned mixed glue solution, wherein the specific surface area of ​​the hard carbon is 6m 2 / g, D50 is 5 microns; the mixture is stirred in vacuum at 30 revolutions per minute and 2500 revolutions per minute for 2 hours;

[0047] S4, adding 30 g of porous alumina to the above mixed solution, and stirring in vacuum at 30 revolutions / min and 2500 rotations / min for 2 hours;

[0048] S5, adding 40 g of polyacrylic acid liquid with a solid content of 40% to the above mixed solution, and stirring in vacuum at a revolution of 30 rpm and a rotation of 500 rpm for 30 minutes;

[0049] S6, passing the deaerated slurry through a 150-mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

[0050] Preparation of the pole piece: The sieved slurry is evenly coated on a 15 μm thick aluminum foil by slurry drawing, dried in a vacuum oven at 120°C for 12 hours, and the obtained pole piece is rolled to a compaction density of 1.2 g / cm 3 The surface density of the obtained electrode is 4.7 mg / cm 2 .

[0051] Example 4

[0052] A method for preparing a negative electrode slurry for a sodium ion battery comprises:

[0053] S1, add 800g of deionized water and 8g of thickener sodium carboxymethyl cellulose (CMC) powder into a 5L planetary stirring device stirrer, stir for 15 minutes at a revolution of 30 rpm and a rotation of 1000 rpm; open the stirring container, scrape the undissolved powder on the stirring and dispersing disk and the wall of the stirrer into the solution, and stir in a vacuum at a revolution of 30 rpm and a rotation of 2000 rpm for 2 hours and 30 minutes; during the period, cool water is passed to prevent the glue solution from overheating; the stirred glue solution is allowed to stand in a vacuum state for 24 hours;

[0054] S2, adding 25 g of single-walled carbon nanotubes into the glue solution, and stirring in vacuum at 30 revolutions / min and 2000 rotations / min for 1 hour;

[0055] S3, adding 1200g of hard carbon, a negative electrode active material of a sodium ion battery, into the above-mentioned mixed glue solution, wherein the specific surface area of ​​the hard carbon is 6m 2 / g, D50 is 5 microns; the mixture is stirred in vacuum at 30 revolutions per minute and 2500 revolutions per minute for 2 hours;

[0056] S4, adding 30g of titanium oxide-coated alumina to the above-mentioned mixed solution, and stirring in vacuum at a revolution of 30 rpm and a rotation of 2500 rpm for 2 hours; the preparation method of titanium oxide-coated alumina comprises the following steps: a1, placing aluminum hydroxide fine powder in ethanol-ether solution for microwave cleaning, and taking it out and drying to obtain clean aluminum hydroxide fine powder, the volume ratio of ethanol to ether in the ethanol-ether solution is 3:4, the concentration of aluminum hydroxide fine powder in the ethanol-ether solution is 400g / L, the microwave cleaning temperature is 15°C, the power is 400W, and the drying temperature is 85°C; the aluminum hydroxide fine powder has a porous structure; a2, dissolving n-butyl titanate in ether and stirring evenly to form titanium ether solution, and then immersing the aluminum hydroxide fine powder in the titanium ether solution for 15 minutes , after filtering and drying, a coated aluminum hydroxide fine powder is obtained, the concentration of n-butyl titanate in the titanium ether solution is 150g / L, the stirring speed is 150r / min, the concentration of the aluminum hydroxide fine powder in the titanium ether solution is 30g / L, and the drying temperature is 45°C; a3, the coated aluminum hydroxide fine powder is placed in a reactor for constant temperature reaction for 2h, and then nitrogen containing water vapor is introduced for 8min, and the reaction is allowed to stand for 25min to obtain titanium oxide-coated aluminum oxide; the temperature of the constant temperature reaction is 190°C, the volume proportion of water vapor in the nitrogen is 8%, and the introduction speed is 40mL / min, and the standing temperature is 120°C; a4, the titanium oxide-coated aluminum oxide is sintered for 2h to obtain a porous coating structure, and the standing sintering temperature is 190°C;

[0057] S5, adding 40 g of polyacrylic acid liquid with a solid content of 40% to the above mixed solution, and stirring in vacuum at a revolution of 30 rpm and a rotation of 500 rpm for 30 minutes;

[0058] S6, passing the deaerated slurry through a 150-mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

[0059] Preparation of the pole piece: The sieved slurry is evenly coated on a 15 μm thick aluminum foil by slurry drawing, dried in a vacuum oven at 120°C for 12 hours, and the obtained pole piece is rolled to a compaction density of 1.1 g / cm 3 The surface density of the obtained electrode is 4.4 mg / cm 2 .

[0060] Example 5

[0061] A method for preparing a negative electrode slurry for a sodium ion battery comprises:

[0062] S1, add 800g of deionized water and 8g of thickener sodium carboxymethyl cellulose (CMC) powder into a 5L planetary stirring device stirrer, stir for 15 minutes at a revolution of 30 rpm and a rotation of 1000 rpm; open the stirring container, scrape the undissolved powder on the stirring and dispersing disk and the wall of the stirrer into the solution, and stir in a vacuum at a revolution of 30 rpm and a rotation of 2000 rpm for 2 hours and 30 minutes; during the period, cool water is passed to prevent the glue solution from overheating; the stirred glue solution is allowed to stand in a vacuum state for 24 hours;

[0063] S2, adding 25 g of single-walled carbon nanotubes into the glue solution, and stirring in vacuum at 30 revolutions / min and 2000 rotations / min for 1 hour;

[0064] S3, adding 1200g of hard carbon, a negative electrode active material of a sodium ion battery, into the above-mentioned mixed glue solution, wherein the specific surface area of ​​the hard carbon is 6m 2 / g, D50 is 5 microns; the mixture is stirred in vacuum at 30 revolutions per minute and 2500 revolutions per minute for 2 hours;

[0065] S4, adding 30g of titanium oxide-coated alumina to the above-mentioned mixed solution, and stirring in vacuum at a revolution of 30 rpm and a rotation of 2500 rpm for 2 hours; the preparation method of titanium oxide-coated alumina comprises the following steps: a1, placing aluminum hydroxide fine powder in ethanol-ether solution for microwave cleaning, and taking it out and drying to obtain clean aluminum hydroxide fine powder, the volume ratio of ethanol to ether in the ethanol-ether solution is 3:4, the concentration of aluminum hydroxide fine powder in the ethanol-ether solution is 400g / L, the microwave cleaning temperature is 15°C, the power is 400W, and the drying temperature is 85°C; the aluminum hydroxide fine powder has a porous structure; a2, dissolving n-butyl titanate in ether and stirring evenly to form titanium ether solution, and then immersing the aluminum hydroxide fine powder in the titanium ether solution for 15 minutes , after filtering and drying, a coated aluminum hydroxide fine powder is obtained, the concentration of n-butyl titanate in the titanium ether solution is 150g / L, the stirring speed is 150r / min, the concentration of the aluminum hydroxide fine powder in the titanium ether solution is 30g / L, and the drying temperature is 45°C; a3, the coated aluminum hydroxide fine powder is placed in a reactor for constant temperature reaction for 2h, and then nitrogen containing water vapor is introduced for 8min, and the reaction is allowed to stand for 25min to obtain titanium oxide-coated aluminum oxide; the temperature of the constant temperature reaction is 190°C, the volume proportion of water vapor in the nitrogen is 8%, and the introduction speed is 40mL / min, and the standing temperature is 120°C; a4, the titanium oxide-coated aluminum oxide is sintered for 2h to obtain a porous coating structure, and the standing sintering temperature is 190°C;

[0066] S5, adding 40 g of polyacrylic acid liquid with a solid content of 40% to the above mixed solution, and stirring in vacuum at a revolution of 30 rpm and a rotation of 500 rpm for 30 minutes;

[0067] S6, passing the deaerated slurry through a 150-mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

[0068] Preparation of the electrode: step 1, adding high-substituted hydroxypropyl cellulose to the slurry and stirring evenly to obtain a dispersed slurry, wherein the concentration of the high-substituted hydroxypropyl cellulose in the slurry is 2%; step 2, coating the dispersed slurry on the current collector, and then constant temperature rolling to obtain a prefabricated negative electrode plate, wherein the current collector is aluminum foil, and the thickness of the aluminum foil is 15 μm; the temperature of the constant temperature rolling is 85° C., and the pressure is 0.3 MPa; step 3, soaking and dissolving the prefabricated negative electrode plate in methanol, taking out and drying to obtain a porous electrode plate, wherein the mass ratio of the prefabricated negative electrode plate to methanol is 1:20, and the drying temperature is 65° C. The solution after dissolution is evaporated to recover the high-substituted hydroxypropyl cellulose.

[0069] Embodiment 1, embodiment 3, embodiment 4 and embodiment 5 are put into button batteries. The specific preparation method is as follows: a metal sodium sheet, a 20-micron-thick polyacrylic acid, and a negative electrode sheet are stacked in sequence into an electrode group, which is loaded into a button battery shell, and an electrolyte with sodium hexafluorophosphate as a solute, ethylene carbonate and propylene carbonate in a volume ratio of 1:1 as a solvent, and a solute concentration of 1 mol / L is added, and the added volume is 200 μL, and the button battery is assembled; the assembled battery is discharged at a constant current of 0.1C to 0V at a current density of 1C=120mA / g at 25°C, and is allowed to stand for 5 minutes, and is charged at a constant current of 0.1C to 2V, and this process is cycled 3 times; and constant current charging and discharging are performed 3 times at different rates (0.2C, 0.5C, 1C, 2C), and the cut-off voltage is consistent with 0.1C.

[0070] After testing, the battery prepared in Example 3, the hard carbon negative electrode has a discharge specific capacity at a 2C rate that is 1.2% higher than that of the negative electrode in Example 1; the battery prepared in Example 4, the hard carbon negative electrode has a discharge specific capacity at a 2C rate that is 7.6% higher than that of the negative electrode in Example 1; the battery prepared in Example 5, the hard carbon negative electrode has a discharge specific capacity at a 2C rate that is 8.9% higher than that of the negative electrode in Example 1.

[0071] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A sodium ion battery negative electrode slurry, characterized in that: The slurry comprises a negative electrode active material, a porous medium, a conductive agent, a binder, a thickener and a solvent, and the mass ratio of the slurry comprises: 80-99.9 parts of the negative electrode active material, 0.1-5 parts of the porous medium, 0.1-10 parts of the conductive agent, 0.1-10 parts of the binder, 0.1-5 parts of the thickener, and 70-300 parts of the solvent; The porous medium adopts porous anatase titanium dioxide or porous alumina, and the particle size distribution D10 is 1 μm, D50 is 5 μm, D90 is 10 μm, and Dmax is 12 μm; the porous medium adopts a porous core-shell composite material, and uses anatase titanium dioxide as the surface layer, wrapping porous alumina to form a porous coating structure.

2. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The negative electrode active material is hard carbon or soft carbon.

3. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The conductive agent is one or more materials selected from the group consisting of conductive carbon black, acetylene black, conductive graphite, single-walled carbon nanotubes and multi-walled carbon nanotubes.

4. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The binder is made of one or more materials selected from styrene-butadiene rubber, polyacrylic acid and polyacrylonitrile.

5. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose.

6. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The solvent used was deionized water.

7. The negative electrode slurry for sodium ion battery according to claim 1, characterized in that: The method for preparing the negative electrode slurry of a sodium ion battery comprises: S1, material preparation: weigh the required raw materials according to the required ratio and dry them in a protective atmosphere; S2, glue preparation: placing the thickener and the solvent in a planetary agitator, stirring them in a vacuum at a revolution of 10-100 rpm and a rotation of 500-7000 rpm for 0.5-12 hours to obtain a glue solution, passing cooling water during the stirring process to prevent the glue solution from being too hot; the obtained glue solution needs to be left to stand for 12-24 hours; S3, dispersion: add the conductive agent to the glue solution, and stir it in a vacuum at a revolution of 10-100 rpm and a rotation of 500-5000 rpm for 0.5-6 hours; then add the negative electrode active material, and stir it in a vacuum at a revolution of 10-100 rpm and a rotation of 500-5000 rpm for 0.25-3 hours; then add the porous medium, and stir it in a vacuum at a revolution of 10-100 rpm and a rotation of 500-5000 rpm for 0.5-3 hours; finally, add the binder, and stir it in a vacuum at a revolution of 10-100 rpm and a rotation of 200-1000 rpm for 0.25-2 hours; S4, degassing: placing the slurry in a vacuum environment of -0.1 MPa for 20 minutes to 3 hours; S5, sieving: the slurry is passed through a 100-300 mesh sieve to obtain the desired sodium ion battery negative electrode slurry.

8. A method for preparing a negative electrode sheet for a sodium ion battery using the negative electrode slurry for a sodium ion battery according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Step 1, adding highly substituted hydroxypropyl cellulose to the negative electrode slurry of the sodium ion battery and stirring evenly to obtain a dispersed slurry, wherein the concentration of the highly substituted hydroxypropyl cellulose in the slurry is 2-3%; Step 2, coating the dispersed slurry on the current collector, and then rolling at a constant temperature to obtain a prefabricated negative electrode sheet, wherein the current collector is an aluminum foil, and the thickness of the aluminum foil is 8-20 μm; the temperature of the constant temperature rolling is 80-90° C., and the pressure is 0.2-0.5 MPa; Step 3, soaking and dissolving the prefabricated negative electrode sheet in methanol, taking it out and drying it to obtain a porous electrode sheet, wherein the mass ratio of the prefabricated negative electrode sheet to methanol is 1:20-30, and the drying temperature is 60-70°C. The dissolved solution is evaporated to recover the highly substituted hydroxypropyl cellulose.

Citation Information

Patent Citations

  • Negative electrode slurry for sodium-ion battery, negative pole piece and battery

    CN107204467A

  • Negative electrode material and preparation method thereof, negative electrode plate and battery

    CN114551836A